Magnetic-field-assisted laser cladding in the preparation of a crack-free Fe-Cr-Mo-C-Y-B amorphous coating on steel. (1st February 2020) - Zhang, Qi; Zhang, Peilei; Yan, Hua; Yu, Zhishui; Wu, Di; Shi, Haichuan; Li, Shaowei; Tian, Yingtao
ABSTRACT: A crack-free Fe-Cr-Mo-C-Y-B amorphous coatings has been prepared on the surface of Q235 steel by the method of magnetic-field-assisted laser cladding. The uniformity of the distribution of elements in the coating is increased by alternating the magnetic field, which increases the plastic toughness of the coating. The mechanical behaviour of indentation points after nanoindentation of the coated sample was observed by transmission electron microscopy.